2020
DOI: 10.1007/s10886-020-01227-w
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Methyl-Branched Cuticular Hydrocarbons for Successful Host Recognition by the Larval Ectoparasitoid Holepyris sylvanidis

Abstract: Cuticular hydrocarbons (CHCs) of host insects are used by many parasitic wasps as contact kairomones for host location and recognition. As the chemical composition of CHCs varies from species to species, the CHC pattern represents a reliable indicator for parasitoids to discriminate host from non-host species. Holepyris sylvanidis is an ectoparasitoid of beetle larvae infesting stored products. Previous studies demonstrated that the larval CHC profile of the confused flour beetle, Tribolium confusum, comprises… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
(122 reference statements)
1
16
0
Order By: Relevance
“…The liquid aggregate state of methyl-branched alkanes might be relevant for eliciting trail-following behavior in H. sylvanidis. This suggestion is supported by our previous study, which showed that methyl-branched CHCs on the cuticle of T. confusum larvae are exploited by H. sylvanidis females for host recognition when directly contacting the host larvae (Awater-Salendo et al 2020).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The liquid aggregate state of methyl-branched alkanes might be relevant for eliciting trail-following behavior in H. sylvanidis. This suggestion is supported by our previous study, which showed that methyl-branched CHCs on the cuticle of T. confusum larvae are exploited by H. sylvanidis females for host recognition when directly contacting the host larvae (Awater-Salendo et al 2020).…”
Section: Discussionsupporting
confidence: 78%
“…Holepyris sylvanidis discriminates between a host and a non-host species by a specific pattern of methyl-branched alkanes. The host-specific CHC pattern is common to the cuticle of different host beetle species (Awater-Salendo et al 2020 ). Hexane extracts of host larvae deposited as trails elicit trail-following behavior of H. sylvanidis .…”
Section: Introductionmentioning
confidence: 99%
“…These consisted of seven nalkanes (C25-C31), six 3-and 4-methyl-branched alkanes and seven internally methylbranched alkanes of which one was a dimethyl alkane (Table S2). The RIs of all identified CHCs did not differ by more than ± 4 from the RI values proposed by the literature (Lockey 1978;Alnajim et al 2019;Awater-Salendo et al 2020). The dominant CHCs in both naïve females and males were n-C29, 3-MeC27, 13-MeC27 and n-C27, all with a higher proportion than 10% (Table S2).…”
Section: Cuticular Hydrocarbonsmentioning
confidence: 55%
“…FASs are involved in the production of methyl alkanes (Blomquist & Ginzel, 2021; Holze et al, 2021). In comparison to n -alkanes (linear alkanes), methyl alkanes were shown to be more important in cue recognition (reviewed in van Zweden & d’Ettorre, 2010) and to mediate detection of T. castaneum larvae by parasitoids (Awater-Salendo et al, 2020). The regulation of methyl alkanes upon immune stimulation has been reported in other host-parasite systems as well (Baracchi et al, 2012; Richard et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation